The Impact of Employee Empowerment on Intellectual Capital and Organizational Citizenship Behavior: Moderating role of Demographic - et. al., Nawzad Majeed Hamawandy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recently, human resources management measured as the most worth able resource has been the center of approaches, activities and it plays an important role in promoting the objectives and goals of the organization. In fact the financial paradigms do not meet the requirements and expectations of the organization, it has led organizations to seek other paths to achieve competitive advantages. In this study, the growth of intellectual capital and organizational citizenship behavior can be taking new approaches in to account field. Practices for development going beyond the role of recognized expectations needs vital infrastructures. Therefore, empowerment is an important element to plays positive role to describing about social exchange of organizational citizenship behavior. Alternatively, in the economy of knowledge-based, the intellectual capital is the creating knowledge and sharing to enhance enterprise values. The study based on descriptive analysis and it examine the relationship between employee’s empowerment, intellectual capital and organizational citizenship behavior. To the theoretical data collection and to extract initial factors and indicators, library and Internet resources were used and questionnaire was used to gather the data needed to evaluate the assumptions. In this research, random method sampling has been used and Pearson's correlation coefficient was used to analysis data. The findings of study state that a positive and significant relationship occurs between dimensions of employee’s empowerment with growth of Intellectual capital and organizational citizenship behavior. On the other hand, becoming more empowered, employees` growth of intellectual capital has increased and the organization will enjoy more progressive staff